2016
DOI: 10.1519/jsc.0000000000001355
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer–Related Lymphedema and Resistance Exercise: A Systematic Review

Abstract: Nelson, NL. Breast cancer-related lymphedema and resistance exercise: a systematic review. J Strength Cond Res 30(9): 2656-2665, 2016-Breast cancer-related lymphedema (BCRL) is characterized by the accumulation of fluid in the interstitial tissues in the arm, shoulder, neck, or torso and attributed to the damage of lymph nodes during breast cancer treatments involving radiation and axillary node dissection. Resistance exercise training (RET) has recently shown promise in the management of BCRL. The aims of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0
16

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(86 citation statements)
references
References 27 publications
(21 reference statements)
4
66
0
16
Order By: Relevance
“…Therefore, the enhancement of the strength of the non-affected arm muscle strength can be used to speculate the improvement of muscle strength in the affected arm. In addition, there were no side effects that caused or aggravated lymphedema during the intervention, which also confirmed the conclusions of previous studies that resistance training does not cause or aggravate lymphedema in the affected side of BC survivors [39][40][41][42][43].…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, the enhancement of the strength of the non-affected arm muscle strength can be used to speculate the improvement of muscle strength in the affected arm. In addition, there were no side effects that caused or aggravated lymphedema during the intervention, which also confirmed the conclusions of previous studies that resistance training does not cause or aggravate lymphedema in the affected side of BC survivors [39][40][41][42][43].…”
Section: Discussionsupporting
confidence: 89%
“…Due to improved medical treatment options and early screening and detection, breast cancer survival rates have increased significantly in the last years, and more than 80% of patients can be cured [1]. Given the improved survival rates, dealing with treatment-associated side effects such as secondary lymphedema (SL) is a new challenge in cancer care [2]. SL is likely to occur after the surgical removal of lymph nodes or in conjunction with radiotherapy [3].…”
Section: Introductionmentioning
confidence: 99%
“…The ACSM guidelines indicate specific exercise programs oriented towards impairments associated with disease and medical treatment [8]. Strength exercise does not have any negative effects on an existing SL [9]; instead, it has beneficial effects such as improvement of strength [2] and lower exacerbation rates [10]. …”
Section: Introductionmentioning
confidence: 99%
“…Nelson (2016) reviewed the effect of resistance training on lymphedema in breast cancer patients. In 6 randomized controlled trials, involving 805 breast cancer survivors, he concluded that breast cancer survivors can perform high-enough intensity resistance exercise training to increase strength muscle without any changes in lymphedema status (27). Keilani et al (2016) reviewed the influence of the resistance training on secondary lymphedema in breast cancer patients (28).…”
Section: Resultsmentioning
confidence: 99%